1981
DOI: 10.1128/jvi.39.2.447-454.1981
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and structural relationships of the surface antigens of hepatitis B virus, ground squirrel hepatitis virus, and woodchuck hepatitis virus

Abstract: The surface antigens of human hepatitis B (HBsAg), ground squirrel hepatitis (GSHsAg), and woodchuck hepatitis (WHsAg) viruses were compared serologically, and their major polypeptides were analyzed by sodium dodecyl sulfatepolyacrylamide gel electrophoresis and tryptic peptide mapping. Results showed that both GSHsAg and WHsAg are antigenically cross-reactive, that their major pairs of polypeptides have identical mobilities on sodium dodecyl sulfate gels, and that the major polypeptides of GSHsAg and WHsAg mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 21 publications
3
18
1
Order By: Relevance
“…Liver biopsies were not available for observation, and the lack of detectable surface antigenemia and of increased serum enzymes suggested that the animal experienced a subclinical infection. Although cross-reactivities between the major antigen-antibody systems of WHV and HBV have been reported (7,8,11,13,33), we did not detect cross-reactive antibodies in this chimpanzee when we used the commercial HBV RIA systems. The antibody responses of the chimpanzee, detected by the present woodchuckspecific RIAs (25,34; Ponzetto et al, submitted for publication), indicated that the responses were specific for WHV infection.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Liver biopsies were not available for observation, and the lack of detectable surface antigenemia and of increased serum enzymes suggested that the animal experienced a subclinical infection. Although cross-reactivities between the major antigen-antibody systems of WHV and HBV have been reported (7,8,11,13,33), we did not detect cross-reactive antibodies in this chimpanzee when we used the commercial HBV RIA systems. The antibody responses of the chimpanzee, detected by the present woodchuckspecific RIAs (25,34; Ponzetto et al, submitted for publication), indicated that the responses were specific for WHV infection.…”
Section: Discussioncontrasting
confidence: 57%
“…The eastern woodchuck and the woodchuck hepatitis virus (WHV) are currently under investigation as a naturally occurring model system for hepatitis B virus (HBV) infection in humans. Both WHV and HBV are characterized by similar structural and genomic compositions (9,11,12,28,29), and infection with either virus can lead to analogous pathology in their respective hosts (22,26,27,29,30,31). An important marker for the study of HBV infection in humans has been the detection of viral core antigen in liver biopsies (1,5,35).…”
mentioning
confidence: 99%
“…Substitutions within the major hydrophilic region of HBsAg (aa 104-172) were found in most patients (one or two amino acids per patient), except patients S4 and S8 (Table II). The immunodominant a determinant (aa 124-147) [Feitelson et al, 1981] of HBsAg had no variation in any of the isolates, except variants S2.2 (A128V), S 2.3 (I126T), and S4.4 (I126T), all the substitutions were within the first hydrophilic loop of the a determinant (Table II). The stop codon mutations in variant S1.1, S7.4, and S8.1 were observed in the coding sequence of HBsAg.…”
Section: Analysis Of the Pre-s-s Genomic Regionmentioning
confidence: 97%
“…Hepatitis B virus (HBV), ground squirrel hepatitis virus (GSHV), woodchuck hepatitis virus (WHV) and duck hepatitis B virus (DHBV) comprise a group of infectious agents which share many biochemical characteristics (1)(2)(3)(4)(5)(6). The virions of each are surrounded by an envelope of surface antigen reactive determinants which are immunologically distinct and which reside on a family of virus-encoded polypeptides whose number and sizes vary (2)(3)(4)(6)(7)(8)(9). Virus nucleocapsids, or core particles, have been isolated by treatment of serumderived virions with nonionic detergent or directly from viruses is circular, heat linearization demonstrates that even after the DNAp reaction, a nick exists in each of the DNA strands (6,19).…”
mentioning
confidence: 99%